Intraluminal Tubal Endometriosis Mimicking Hydrosalpinx: Report of an Unusual Case - E, Ozturk; MG, Ugur; A, Aydın; O, Balat; H, Kalaycı (IIUM Medical Journal Malaysia, 2010)
Endometriosis is an estrogen-dependent disease causing pelvic pain and infertility and there is still limited knowledge of the pathogenesis. Hydrosalpinx is commonly seen in a heterogeneous spectrum of pathologies of distal tubal occlusion. In general, collection of fluid in uterine tubes occur as the end stage of pyosalpinx or as the advenced stage of endometriosis with pelvic adhesion. In this report we present a very rarely seen case that is called intraluminal tubal endometriosis mimicking hydrosalpinx without pelvic adhesion in an infertile patient. The clinical features and the management of intraluminal tubal endometriosis case which is very rare cause of enlarged tuba uterina in an infertile patient discussed.